(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the current capacity for implementing hypertension prevention activities at commune health centers (CHCs) of Ha Noi in 2023. Study design: Cross-sectional study. Results: The rate of CHCs with health insurance for examination and treatment of hypertension is 66.49%. The proportion of doctors participating in diabetes diagnosis and treatment at health stations in the area is 17.70%. The percentage of health stations with less than 50% of essential medications is also high, at 84.28%. Health stations are not fully equipped with the necessary medications for treatment as stipulated by the Ministry of Health. The main medications provided at these stations are Amlodipin (58.72%) and Enalapril (41.97%). Conclusion: Hypertension management activities at the grassroots health level have not been fully and widely deployed in the city. It is necessary to add more human resources and fully prepare medicine for effective treatment management, especially CHCs in countryside and moutainous areas.